Penerapan Model Problem Based Learning (PBL) untuk Meningkatkan Hasil Belajar Peserta Didik pada Mata Pelajaran Matematika - Much. Iqbal; Sati Sati; Nurkholis Nurkholis (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research was motivated by the low learning outcomes of students in Mathematics subjects. This research aims to improve student learning outcomes in mathematics subjects through the application of the Problem Based Learning model. The research method used in this research is classroom action research (PTK) which consists of 2 cycles, where each cycle consists of 1 meeting with activity stages including planning, implementation, observation and reflection. In the initial conditions, student learning outcomes were still low. This is because teachers have not implemented innovative learning models. Thus, students are less able to find, analyze and conclude the area of ​​a flat rectangular shape. Therefore, Classroom Action Research (PTK) was carried out by applying the Problem Based Learning (PBL) model with the hope that the final conditions would experience an increase in student learning outcomes. The results of the research showed that in the pre-cycle the percentage of learning outcomes was 35.71%, there was an increase in student learning outcomes in cycle I of 64.29% and cycle II of 85.71% after implementing the Problem Based Learning (PBL) learning model in Mathematics learning .